PENINGKATAN HASIL BELAJAR PKN MENGGUNAKAN TIPE STUDENT TEAMS ACHIEVEMENT DIVISION KELAS V SEKOLAH DASAR - Ariyo, Ariyo; Asran, Mastar; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to describe the civics learning  outcomes by using student teams achievement division in the fifth grade public elementary school 28 South Pontianak. The method that used in this research was descriptive method with a form of classroom action research. The subject in this research were teacher and 23 students of class V. The procedure in this research consists of four step: planning, action, observation, and reflection. The data collection technique that used in this research were direct observation technique and scrutiny documents. The data collection technique that used in this research were observation sheets and sheets of scrutiny documents. This research result: 1) the ability of teacher to plan learning in cycle 1, with an average score of 3,54. In cycle 2 and cycle 3 becomes 3,72 to 3,88. 2) the ability of teacher in implementing the learning in the first cycle, with an average score of 3,36, in cycle 2 to 3,61, in cycle 3 to 3,85. 3) An increase in the average learning outcomes of class V at first cycle is 68,61, the second cycle increase to 77,27 and in cycle 3 into 86,52. Keywords: Learning Outcomes, Civics Learning, STAD